Kwame Nkrumah's contribution to Pan-African agency an Afrocentric analysis - Poe, D.Zizwe. (London Routledge, 2003)
This study analyzes contributions made by Kwame Nkrumah (1909-1972) to the development of Pan-African agency from the 1945 Pan-African Congress in Manchester to the military coup d'etat of Nkrumah's government in February 1966.
Includes index
Keywords: Kwame Nkrumah